1997
DOI: 10.1180/minmag.1997.061.405.06
|View full text |Cite
|
Sign up to set email alerts
|

Ilmenite from the Chavara deposit, India: a critical evaluation

Abstract: The mineralogical status of ilmenite from a prominent modern placer deposit of India is illustrated using different techniques. Compositional, powder XRD, TGA and SEM analyses prove that consistent low temperature alteration took place in Chavara ilmenite leading to the formation of a pseudorutile-hydrated-ilmenite stage. Except for the indication of a geochemical zonation at the southern tip of the deposit, the Chavara ilmenite points to a common origin throughout its 22 km stretch along the coast. We advocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The Ti/ (Ti + Fe) ratio indicates that the Chavara fractions generally fall in the fields of 'Hydrated Ilmenite' and 'Pseudorutile' stages, and extend to that between 'Pseudorutile' and the most altered 'Leucoxene' stages (Table 1). This qualitative difference confirms the higher alteration undergone by the Chavara ilmenite (Nair et al, 1995;Ramakrishnan et al, 1997;Nair et al, 2002). Fig.…”
Section: Chemical and Mineralogical Characteristicssupporting
confidence: 84%
See 1 more Smart Citation
“…The Ti/ (Ti + Fe) ratio indicates that the Chavara fractions generally fall in the fields of 'Hydrated Ilmenite' and 'Pseudorutile' stages, and extend to that between 'Pseudorutile' and the most altered 'Leucoxene' stages (Table 1). This qualitative difference confirms the higher alteration undergone by the Chavara ilmenite (Nair et al, 1995;Ramakrishnan et al, 1997;Nair et al, 2002). Fig.…”
Section: Chemical and Mineralogical Characteristicssupporting
confidence: 84%
“…In spite of the commercial implications of the deposit due to its high quality ilmenite and its exploitation from the beginning of the 20th century, not many studies have focused on the alteration patterns of beach ilmenite (Viswanathan, 1957;Gillson, 1959;Ramakrishnan et al, 1997). Studies on the different magnetic fractions of beach ilmenite concentrate are useful to delineate the alteration trends and chemical variations of the mineral (Frost et al, 1986;Suresh Babu et al, 1994) that, in turn, have a bearing on the economic value of its deposit.…”
Section: Introductionmentioning
confidence: 98%
“…Ilmenites present in saprolites and soils of group SJR-sap, as well as in group SJR-sed are weathered, whereas this is not clearly observed in group SL-sap. Weathering of ilmenite under oxidizing conditions has been frequently reported (Anand and Gilkes, 1984;Ramakrishnan et al, 1997). In group SJR-sap, ilmenite grains show altered surfaces, characterized in thin section by a pellicular, dotted and/or complex alteration pattern, similar to the pattern described by Anand and Gilkes (1984) for a lateritic layer in Australia.…”
Section: Ilmenite and Anatasementioning
confidence: 82%
“…Johnson et al, 1977). After reworking and redeposition in beaches, relatively little further leaching appears to affect the ilmenite, since Ramakrishnan et al (1997) found only modest changes in Ti/Fe ratios in sample traverses perpendicular to the coastline.…”
Section: Source Of High-ti Ilmenite Of the Chavara Depositmentioning
confidence: 87%